Representation of Lebanese Women’s Identity in Capernaum Film - Bernadette, Kezia Sharron (Journal of Arts and Education, 2024)
The film Capernaum, directed by Nadine Labaki, offers a poignant portrayal of Lebanese women's identity and delves into the complexities of gender, culture, and society. The study aims to critically analyze the depiction of Lebanese women's identity through a qualitative study, examining cinematic elements, character identities, and narrative structure. The film's portrayal of female characters, Souad, Sahar, and Rahil, highlights societal expectations and cultural contexts that shape women's identities. These characters are shaped by societal expectations and cultural and social contexts, including gender-based violence and traditional gender roles. The study employs textual analysis to investigate the representation of Lebanese women's identity and patriarchal culture in the film. Moreover, the findings reveal that women's identity concepts in Capernaum are characterized by the need to meet beauty standards, dependency on men, obedience to men, and adherence to traditional gender roles. The film also portrays the struggles of women in patriarchal society, including feelings of powerlessness, insecurity, and low self-esteem. The study contributes to academic knowledge by providing a nuanced understanding of Lebanese women's identity and its representation in the film Capernaum, enriching the analysis of film studies, and offering insights into the societal expectations and cultural contexts that shape women's identities.